The CHOICE pilot project: Challenges of implementing a combined peer work and shared decision‐making programme in an early intervention service. Issue 5 (12th December 2017) - Simmons, Magenta B.; Coates, Dominiek; Batchelor, Samantha; Dimopoulos‐Bick, Tara; Howe, Deborah
Abstract : Aim: Youth participation is central to early intervention policy and quality frameworks. There is good evidence for peer support (individuals with lived experience helping other consumers) and shared decision making (involving consumers in making decisions about their own care) in adult settings. However, youth programs are rarely tested or described in detail. This report aims to fill this gap by describing a consumer focused intervention in an early intervention service. Methods: This paper describes the development process, intervention content and implementation challenges of the Choices about Healthcare Options Informed by Client Experiences and Expectations (CHOICE) Pilot Project. This highly novel and innovative project combined both youth peer work and youth shared decision making. Results: Eight peer workers were employed to deliver an online shared decision‐making tool at a youth mental health service in New South Wales, Australia. The intervention development involved best practice principles, including international standards and elements of co‐design. The implementation of the peer workforce in the service involved a number of targeted strategies designed to support this new service model. However, several implementation challenges were experienced which resulted in critical learning about how best to deliver these types of interventions. Conclusions: Delivering peer work and shared decision making within an early intervention service is feasible, but not without challenges. Providing adequate detail about interventions and implementation strategies fills a critical gap in the literature. Understanding optimal youth involvement strategies assists others to deliver acceptable and effective services to young people who experience mental ill health.